Machine Learning with Apache Spark Quick Start Guide : Uncover patterns, derive actionable insights, and learn from big data using MLlib /: Uncover patterns, derive actionable insights, and learn from big data using MLlib. (2018) - Quddus, Jillur
No abstract available